An In-vitro Study for Pharmaceutical and Analytical Profile of Herbal Drug: Panchpallav Gargles - Riya Rajendra Rathor; Renu Bharat Rathi (Journal of Clinical and Diagnostic Research)
Introduction: Contemporary pharmaceutical analytical methods and standardisation must be employed to examine the composition of various Ayurvedic medications. Panchpallav Gargles (Kavala), which are prescribed for oral cavity ailments, are mentioned in Bhavprakash by Acharya Bhavmishra. This formulation is suggested in the form of decoction (Kashaya Kalpana) for mouthwash (mukha dhavana) in diseases of the mouth and throat (Mukhagata and Galagat rogas). Panchpallav Gargles is recommended due to their ease of preparation, pleasant and palatable taste, longer shelf life, and ease of administration. Aim: To study the physicochemical parameters of Panchpallav Gargles through an analytical investigation aimed at determining the fundamental properties. Materials and Methods: This in-vitro study was conducted at the Dattatraya Ayurved Rasashala of the Mahatma Gandhi Ayurved College and Research Centre, Salod, Hirapur, Wardha, Maharashtra, India over a period of one year and conducted the pharmaceutical manufacture and analytical analysis of the mouthwash. In present in-vitro study, three batches of gargles were prepared following the reference from Bhavprakash by Acharya Bhavmishra. A constant temperature of 90 to 100 °C was maintained throughout the procedure, and the average time required for the preparation of Panchpallav gargles was two days. The formulation was tested for physicochemical analysis, microbiological characteristics, and organoleptic criteria, including colour and smell. The analytical testing required 15 days to yield the findings. Results: The analytical standards for the Gargles were 5.2 for pH and 1.45 for refractive index, respectively. No microbial contamination was identified in the gargles. Conclusion: The outcomes of the standardisation meet the requirements specified in the Ayurvedic Pharmacopoeia of India (API). Additionally, its usage showed no Adverse Drug Reactions (ADRs) or side effects in the paediatric population and yielded better results in cases of acute pharyngitis.